Effects of different amounts of corms and planting depths of corms on flower and corm yield of saffron (Crocus sativus L.) - Ffatemeh Moallem Banhangi; Parviz Rezvani Moghaddam; Ghorban Ali Asadi; Surur Khorramdel (Zirā̒at va Fanāvarī-i Za̒farān, 2019)
In order to study the effect of different amounts of corms and planting depths of corms on flower and corm yield of saffron, an experiment was conducted in a factorial layout based on complete randomized block design with three replications at the Agricultural Research Station, Faculty of Agriculture, Ferdowsi University of Mashhad, Iran during 2015- 2016 growing seasons. The experimental treatments were all combination of four quantity of corms (7, 8, 9 and 10 t/ha) and three planting depth (10, 15 and 20 cm). The results showed that different quantity and planting depth of saffron corms had significant effects on the most of the studied criteria. The results revealed that flower yield, stigma dry weight, number of flowers and replacement corms per square meter increased by increasing the amount of corm by 9 t/ha and reduced planting depth by 10 cm. The maximum replacement corms yield was obtained in 8 t/ha corm treatment which was 33.25 percent higher than 7 t/ha and 15.99 percent was higher than 10 t/ha corm treatments. The maximum and minimum replacement corms yield were shown in 10 and 20 cm planting depth, respectively. The higher number of replacement corms (173 corm in m2) were obtained in 10 t/ha corms, Therefore, increasing the amount of corms from 7 to 10 t/ha will increase the number of replacement corms by 101 percent while there were no significant differences between the rests of treatments. According to the low yield of saffron in the first year, it seems increasing the amount of corm till the optimum range and reducing the planting depths of corms will increase saffron flowers yield in the first year and lead to produce bigger replacement corms for next years. Hence, optimum amount of corm and planting depths will increase farmers’ income in the first year.